Morphological and molecular evidence support the intertidal barnacle Octomeris intermedia Nilsson-Cantell, 1921 (Thoracica, Chthamalidae) as a valid species in Indo-Pacific waters - Benny K. K. Chan; Yao Fong Tsao; Monthon Ganmanee (My University, 2020)
Octomeris is a chthamalid intertidal barnacle with eight shell plates. There are currently two species of such barnacles: O. brunnea Darwin, 1854 (type locality in the Philippines), common in the Indo-Pacific region, and O. angulosa Sowerby, 1825, only recorded in South Africa. Octomeris intermedia Nilsson-Cantell, 1921, identified from the Mergui Archipelago in Myanmar, was considered to be conspecific with O. brunnea by Hiro (1939) based on samples collected in Taiwan. The morphological differences in shell and opercular plates between O. brunnea and O. intermedia are believed to be intra-specific variations due to different degrees of shell erosion. In the present study, the genetic and morphological differentiations of Octomeris in the Indo-Pacific region were examined. This study found two molecular clades (with inter-specific differences) based on the divergence in the COI genes, and the species also have distinct geographical distributions. The Octomeris brunnea clade covers samples collected from the Philippines and Taiwan waters and the other clade, which we argue is O. intermedia , is distributed in Phuket and Krabi, Thailand and Langkawi, Malaysia. Phuket and Krabi are located approximately 300 km south of the Mergui Archipelago, the type locality of O. intermedia . The morphology of samples collected from Thailand fits the type description of O. intermedia in Nilsson-Cantell (1921). Our study concludes that O. intermedia is a valid species based on morphological and molecular evidence.
Keywords: Thoracica; Archipelago; Type locality; Intermedia; Indo-Pacific; Marine Biology and Ecology Research